Quantification of gold nanoparticle cell uptake under controlled biological conditions and adequate resolution. (April 2014) - Rothen-Rutishauser, Barbara; Kuhn, Dagmar A; Ali, Zulqurnain; Gasser, Michael; Amin, Faheem; Parak, Wolfgang J; Vanhecke, Dimitri; Fink, Alke; Gehr, Peter; Brandenberger, Christina
Aim: We examined cellular uptake mechanisms of fluorescently labeled polymer-coated gold nanoparticles (NPs) under different biological conditions by two quantitative, microscopic approaches.Materials & methods: Uptake mechanisms were evaluated using endocytotic inhibitors that were tested for specificity and cytotoxicity. Cellular uptake of gold NPs was analyzed either by laser scanning microscopy or transmission electron microscopy, and quantified by means of stereology using cells from the same experiment.Results: Optimal inhibitor conditions were only achieved with chlorpromazine (clathrin-mediated endocytosis) and methyl-β-cyclodextrin (caveolin-mediated endocytosis). A significant methyl-β-cyclodextrin-mediated inhibition (63–69%) and chlorpromazine-mediated increase (43–98%) of intracellular NPs was demonstrated with both imaging techniques, suggesting a predominant uptake via caveolin-medicated endocytois. Transmission electron microscopy imaging revealed more than 95% of NPs localized in intracellular vesicles and approximately 150-times more NP events/cell were detected than by laser scanning microscopy.Conclusion: We emphasize the importance of studying NP–cell interactions under controlled experimental conditions and at adequate microscopic resolution in combination with stereology. Original submitted 10 July 2012; Revised submitted 23 January 2013